Diaphragm‐based optical fiber sensor for pulse wave monitoring and cardiovascular diseases diagnosis. Issue 10 (1st July 2019) - Wang, Jingyi; Liu, Kewei; Sun, Qizhen; Ni, Xiaoling; Ai, Fan; Wang, Senmao; Yan, Zhijun; Liu, Deming
Abstract: Arterial pulse wave has been considered as a vital sign in assessment of cardiovascular diseases. Noninvasive pulse sensor with compact structure, immunity to electro‐magnetic interference and high sensitivity is the research focus in recent years. While, optical fiber biosensor is a competitive option to meet these needs. Here, a diaphragm‐based optical fiber pulse sensor was proposed to achieve high‐precision radial pulse wave monitoring. A wearable device was developed, composed of a sports wristband and an aluminum diaphragm‐based optical fiber sensor tip of only 1 cm in diameter, which was highly sensitive to the weak acoustic signal. In particular, coherent phase detection was adopted to improve detection signal‐to‐noise ratio, so as to recover the high‐fidelity pulse waveforms. A clinical experiment was carried out to detect and morphological analyze the pulse waveforms of four subjects, the results of which preliminarily demonstrated the feasibility of pulse diagnosis method. The proposed pulse fiber sensor provides a comfortable way for pulse diagnosis, which is promising in early cardiovascular diseases indicating. Abstract : Arterial pulse wave has been considered as a vital sign in assessment of cardiovascular diseases. Optical fiber biosensor has competitive characteristics of compactness, immunity to electro‐magnetic interference and high sensitivity. Here, a diaphragm based optical fiber pulse sensor is proposed and made into wearable device to achieve high‐precision radial pulse wave monitoring, which provides a comfortable way for pulse diagnosis, promising in early cardiovascular diseases indicating.